Chapter 6: Vuv spectroscopy of solar plasma - Mohan A. (My University, 2025)
VUV spectroscopic diagnostics make use of information contained in the measured intensities and profiles of the spectral lines. Access to images and spectra of hot plasma in UV, EUV, and X- ray regions have provided basic tools to address the fundamental problems in the outer solar atmosphere. Observations of coronal lines have been recognized as important means of investigating the physical properties of coronal plasma and addressing the questions, which are in the forefront of space physics, such as coronal heating and solar wind acceleration. © 2008 World Scientific Publishing Co. Pte. Ltd.